EVALUASI STUDI ASPEK ERGONOMI (Studi Kasus di Perusahaan Plastik Setia Kawan Purwokerto) - Ngadiman Harwanti Nur Ulfah (Kesmas Indonesia, 2010)
ABSTRACT Occupational safety and health right as well as every labor is also a prerequisite for improving productivity. But still many companies have not concern to the aspect of occupational safety and health through the application of ergonomic principles. Plastics factory Setia Kawan Purwokerto is one of the large scale industrial production of plastics to provide market demand in the region of Central Java and West Java. Although not using chemicals in the production process, but the work system and work environment at this company are at risk of workplace accidents. The goal of this research is to determine the application of ergonomics principles in plastics factory Setia Kawan Purwokerto. Data obtained by using ergonomic evaluation model of the International Labor Office (ILO). The results of data analysis shows that the achievements of the implementation aspects of ergonomics are 76 items (59,37%), the number of findings of the priority actions that must be done are 36 items (28,1%). Thus, it can be concluded that the achievements of the implementation of a comprehensive ergonomic aspects into categories including less. Advised the company needs to immediately follow-up findings priority to ensure the safety, health, and worker productivity. Keywords: Evaluation, Ergonomic, Company Kesmasindo: Vol 3(1) 2010;8-18